Oczekiwania rodziców wobec edukacji seksualnej dzieci i młodzieży z lekką niepełnosprawnością intelektualną - Buchnat, Marzena; Waszyńska, Katarzyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The role of parents in supporting the children’s psychosexual development is extremely significant. It is them who introduce first in the system of values, rules, behavioral standards, they teach how to express feelings and emotions and this is why the family home is the best place to start sexual education. It is very difficult for many parents to transfer knowledge about sexuality to children, especially for the parents of children with mental disability. They present different attitudes towards the children’s sexuality, which imply how they lead the education on this topic. Conducted research aimed at exploring the parents’ opinions on sexual education at home. Research results showed a range of difficulties (among others insufficient preparation or knowledge) concerning the conversations with children about their psychosexual development. It is necessary to support the parents with knowledge, information as well as with competences and skills in sexual education of children.